Fracture Toughness Analysis of Automotive-Grade Dual-Phase Steel Using Essential Work of Fracture (EWF) Method - M R, Sunil Kumar; Schmidová, Eva; Konopik, Pavel; Melzer, Daniel; Bozkurt, Fatih; Londe, Neelakantha, V (MDPI, 2020)
Fracture toughness determination of dual-phase DP450 steel using the essential work of fracture (EWF) methodology is the major focus of this research work. The EWF method is used for the determination of fracture toughness of thin sheets in a plane stress dominant condition. The EWF method is discussed in detail with the help of DP450 steel experimental results. Double edge notched tension (DENT) specimens with fatigue pre-crack and without fatigue crack (notched) have been used for testing. Specific essential work of fracture (w(e)), crack tip opening displacement (delta(e)(c)) and crack tip opening angle (psi(e)) parameters were used for the comparative analysis. High-intensity laser beam cutting technology was used for the preparation of notches. Fracture toughness values of fatigue pre-cracked and notched samples were compared. The effect of notch tip radius and fatigue crack on the fracture toughness values were analysed. Digital image correlation (DIC) technology was used for the identification of local strain distribution and validation of the methodology. Fractured surfaces were examined by a scanning electron microscope (SEM) to analyse the fracture morphology and stress state.
Analýza lomové houževnatosti dvoufázové oceli pro automobilový průmysl s využitím metody Essential Work of Fracture (EWF)
Keywords: essential work of fracture (EWF); double edge notch tension (DENT); DP450; fracture toughness; essential work of fracture (EWF); napnutí zářezu s dvojitým okrajem (DENT); DP450; lomová houževnatost